Multi-scale correlative microscopy investigation of both structure and chemistry of deformation twin bundles in Fe-Mn-C steel. - Marceau, R; Gutierrez-Urrutia, I; Herbig, M; Moore, K; Lozano-Perez, S; Raabe, D (2013)
A multi-scale investigation of twin bundles in Fe-22Mn-0.6C (wt%) twinning-induced plasticity steel after tensile deformation has been carried out by truly correlative means; using electron channelling contrast imaging combined with electron backscatter diffraction, high-resolution secondary ion mass spectrometry, scanning transmission electron microscopy, and atom probe tomography on the exact same region of interest in the sample. It was revealed that there was no significant segregation of Mn or C to the twin boundary interfaces.